2017
DOI: 10.3126/ijasbt.v5i4.18637
|View full text |Cite
|
Sign up to set email alerts
|

Field Assessment of Onion Genotypes for Resistance against Purple Blotch Complex (Alternaria porri And Stemphylium vesicarium) under Artificial Epiphytotic Conditions in Indian Punjab

Abstract: Forty-one genotypes of onion were evaluated for their relative response to purple blotch complex caused by Alternaria porri and Stemphylium vesicarium under artificial epiphytotic condition in field during Rabi 2014-2015 and 2015-2016. Significant variation in disease severity among the onion genotypes was found over two years but the pooled analysis revealed that most of the variations were due to genotype x year interaction. None of the genotypes exhibited resistance to the disease complex. Of the test genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The authors stated that it is explained by the deterioration of physiological processes of the host by the pathogen, and consequently, retards the yield and yield-related traits of the crop. Previous studies also reported that disease and yield-related parameters had strong and negative correlations (Abubakar and Ado, 2015;Yadav et al, 2017) and could result in considerable yield reductions. These authors also reported that growth and yield-related traits of onion had strong and positive correlations with each other during the study.…”
Section: Association Of Purple Blotch Epidemics and Bulb Yield Attrib...mentioning
confidence: 85%
See 1 more Smart Citation
“…The authors stated that it is explained by the deterioration of physiological processes of the host by the pathogen, and consequently, retards the yield and yield-related traits of the crop. Previous studies also reported that disease and yield-related parameters had strong and negative correlations (Abubakar and Ado, 2015;Yadav et al, 2017) and could result in considerable yield reductions. These authors also reported that growth and yield-related traits of onion had strong and positive correlations with each other during the study.…”
Section: Association Of Purple Blotch Epidemics and Bulb Yield Attrib...mentioning
confidence: 85%
“…For the last three to four decades, research reports showed that PB influence had been increasing in different areas of the world and Ethiopia as well (Getachew et al, 2014;Aejaz et al, 2020). At the same time, many PB management options have developed; use of disease-free onion seeds or seedlings, removal of infected debris (Mishra et al, 2014;Shumsun et al, 2014), use of host resistant varieties (Wondirad et al, 2009;Yadav et al, 2017) and applications of fungicide as foliar sprays and seed treatments (Abdel-Hafez et al, 2015;Rashid et al, 2015). Management of PB through cultural approaches could play a limited extent.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier study of Nainwal and Vishunavat, (2016) showed correlation between the severities of the onion diseases with the yield [31]. Yadav et al (2017) also reported highly significant negative correlation of purple blotch disease with bulb yield (r=-0.71, p=.01) and bulb size (r=-.67, p=.01) [32].…”
Section: Bulb Yield and Keeping Qualitymentioning
confidence: 89%
“…It not only affect foliage but bulb formation also and thereby deteriorate both yield and quality of the crop. Report on immune response to purple blotch in primary gene pool of onion is vary but some lines have been identified that shows moder-ate to complete resistance against purple blotch (Yadav et al, 2017). Field screening is still common but identification of useful biomarkers (i.e.…”
Section: Introductionmentioning
confidence: 99%